2016
DOI: 10.1039/c6ra10393f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and free energy profile of base-catalyzed Knoevenagel condensation reaction

Abstract: A reliable theoretical calculation of the free energy profile of a base-catalyzed Knoevenagel reaction shows that hydroxide ion elimination step is rate determining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
1
23
0
1
Order By: Relevance
“…124,125 Here, 4 is used as a basic catalyst and most likely acts as a general or specific base (Table 1 -reaction 19), deprotonating the active methylene compound (as general base) or water (specific base), as no information on the pH of the reaction is provided and in general hydroxide is known to catalyse these reaction types. 126 However, a concern for this reaction is the solubility of the starting materials and products. The product is usually insoluble in water, which leads to phase separation and drives the reaction to completion.…”
Section: Nucleophilic and General/specific Base Catalysismentioning
confidence: 99%
“…124,125 Here, 4 is used as a basic catalyst and most likely acts as a general or specific base (Table 1 -reaction 19), deprotonating the active methylene compound (as general base) or water (specific base), as no information on the pH of the reaction is provided and in general hydroxide is known to catalyse these reaction types. 126 However, a concern for this reaction is the solubility of the starting materials and products. The product is usually insoluble in water, which leads to phase separation and drives the reaction to completion.…”
Section: Nucleophilic and General/specific Base Catalysismentioning
confidence: 99%
“…Theoretical calculations have shown that the elimination of hydroxide to form the final product is the rate limiting step in a similar Knoevenagel condensation in methanol. 24 The polar nature of the ionic liquid would favour this elimination. The binary alkoxide ionic liquids were applied to the Aldol condensation between benzaldehyde and acetone to produce hydroxy ketone 1 and -unsaturated ketone 2 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43] The reaction is usually considered as a probe reaction for evaluating basic strength of the catalysts. [44][45][46] The target product, ethyl-2cyano-3-phenyl acrylate, detected exclusively with all the catalysts studied for the screenings verified by GC and 1 H-NMR analysis ( Figure S3). In the absence of any catalyst, only a negligible BA conversion was observed, even after 4 h (BA conversion ∼ 4 %, see Table 2).…”
Section: Resultsmentioning
confidence: 94%
“…Condensation reactions are very important in synthetic organic chemistry, which finds potential applications in the syntheses intermediates for anti‐hypertensive drugs, pharmaceutical chemicals and natural products from small molecules . The reaction is usually considered as a probe reaction for evaluating basic strength of the catalysts . The target product, ethyl‐2‐cyano‐3‐phenyl acrylate, detected exclusively with all the catalysts studied for the screenings verified by GC and 1 H‐NMR analysis (Figure S3).…”
Section: Resultsmentioning
confidence: 98%